Bu Nyai's Multidimensional Leadership Model in Strengthening Islamic Education in Islamic Boarding Schools - Puput Anggraini; Siti Aimah (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze Bu Nyai's multidimensional leadership model in strengthening Islamic education in Islamic boarding schools (pesantren), specifically how the spiritual, social, managerial, and pedagogical dimensions are implemented simultaneously to shape the quality of student development and institutional governance. This research used a qualitative approach with a case study in a pesantren, involving key informants: caretakers, administrators, students, and guardians. Data were collected through in-depth interviews with the Supervisors, Administrators, and alumni, as well as participant observation, documentation, and a thematic coding process to ensure the validity of the findings. The results indicate that Bu Nyai's leadership model is multidimensional, integrating spirituality with structured management. This is manifested through a pattern of senior student cadre development, the implementation of gender-sensitive leadership that empowers female students, strengthening environmental awareness, and strategic regional collaboration. This model has proven vital in ensuring the strengthening of the quality and sustainability of female Islamic education at Darussalam Islamic Boarding School. This research contributes to formulating the Bu Nyai Multidimensional Leadership Model that integrates spirituality and structural management in the context of female Islamic boarding schools, and has proven vital in cadre formation, empowerment of female students through the Gender-Sensitive Leadership approach, strengthening environmental awareness, and developing regional collaboration to ensure the quality and sustainability of Islamic education for women.